(Link Budget of GEO Satellite (Nile Sat) at Ku-band Frequency) Case of study Tripoli and Sebha - Sana Fadil , Nassir Abuhamoud (Journal of Pure & Applied Sciences, 2019)
The link communication between satellite and the Earth Station is exposed to a lot of impairments such as noise, rain and atmospheric attenuations. The successful implementation of satellite communications need to the efficient system design to ensure robust air links for the communications signals. However, the quality of satellite signals are subject to degradation through the atmosphere due to atmospheric impairments. It is therefore crucial to design for all possible attenuation cenarios before the satellites is deployed. The performance indicator "Link budget" is a tabular method of calculating satellite communication system parameters. Link Budget used to estimate the effectiveness and reliability of the link in satellite communication. The link budget is the compilation of all gains and losses in the satellite communication link. This paper presents the fundamentals of a satellite link budget analysis of GEO satellite (Nile Sat ) to accounting of atmospheric attenuation, signal strength and predict the quality of signal received at the ground station during the atmospheric conditions in Tripoli and Sebha using actual climatic parameters. Evaluation of the satellite link performance also presents. The performance of the satellite link is evaluated in terms of carrier to noise ratios, bit energy-to-noise ratios, bit error rate and link margin.